(untitled) (American Journal of Environment and Climate, 2024)
The expansion of the global population, technological progress, economic growth, and rapid urbanization have induced substantial shifts in lifestyle choices, reshaping consumption patterns. This research aimed to investigate the interrelation between recycling practices in rapidly developing nations, notably China, Brazil, Turkey, Vietnam, Nigeria, and the United Arab Emirates (UAE), while emphasizing the role of the UAE, particularly Abu Dhabi, in mitigating climate change and addressing marine pollution. Furthermore, the study ascertain the significance of recycling practices, specifically concerning plastic and e-waste in the UAE, in contributing to environmental sustainability and promoting cleaner oceans. This endeavor ultimately aimed for more sustainable and conscientious development pathways. The research methodology was founded on established theoretical and conceptual framework developed through an in-depth analysis of variables rooted in the theory of planned behavior. Following the successful collection of data on recycling behaviors related to plastic and e-waste in Abu Dhabi, the data was analysed using the Statistical Package for the Social Sciences (SPSS). The findings from the correlation analysis conducted showed complex correlations between recycling behavior and environmental factors. The positive connections found between “comparing recycling practice” and a favorable “future development pathway,” suggested active recycling involvement and good future perspectives. Similarly, positive correlation between “reducing marine pollution” and “environmental sustainability,” demonstrated a shared environmental conscience. However, a negative link was found between “mitigating climate change” and “reducing marine pollution”, “recycling behavior, showing that respondents with higher priority on mitigating climate change also not in favour to recycle and prioritize for reducing marine pollution.